THE EFFECT OF UNDERSTANDING OF TAX ACCOUNTING , IMPLEMENTATION OF MODERN TAX ADMINISTRATION SYSTEM, AND QUALITY OF TAX SERVICES ON TAXPAYER COMPLIANCE - Ginanjar, Seandy; Anita (Management Science Research Journal, 2023)
This study investigates the influence of understanding of tax accounting, application of modern taxation administration systems, and quality of tax services to tax compliance. A Survey of 52 registered corporate taxpayers in KPP Pratama Cilegon. This study used primary data to obtain important information from respondents using a purposive sampling method. SPSS 23 was used to analyze research purposes, which consist of descriptive statistics and tested hypotheses. The results of this study indicate that understanding of tax accounting and the application of a modern taxation administration system has any significant effect on the tax compliance, while (quality of tax service) has no significant effect on the tax compliance.